Research progress on the application of transcranial magnetic stimulation in spinal cord injury rehabilitation: a narrative review - Wang, Yuhong; Dong, Tingting; Li, Xiahuang; Zhao, Huiyun; Yang, Lili; Xu, Rui; Fu, Yi; Li, Li; Gai, Xuesong; Qin, Dongdong (Frontiers in Neurology, 2023)
Traumatic or non-traumatic spinal cord injury (SCI) can lead to severe disability and complications. The incidence of SCI is high, and the rehabilitation cycle is long, which increases the economic burden on patients and the health care system. However, there is no practical method of SCI treatment. Recently, transcranial magnetic stimulation (TMS), a non-invasive brain stimulation technique, has been shown to induce changes in plasticity in specific areas of the brain by regulating the activity of neurons in the stimulation site and its functionally connected networks. TMS is a new potential method for the rehabilitation of SCI and its complications. In addition, TMS can detect the activity of neural circuits in the central nervous system and supplement the physiological evaluation of SCI severity. This review describes the pathophysiology of SCI as well as the basic principles and classification of TMS. We mainly focused on the latest research progress of TMS in the physiological evaluation of SCI as well as the treatment of motor dysfunction, neuropathic pain, spasticity, neurogenic bladder, respiratory dysfunction, and other complications. This review provides new ideas and future directions for SCI assessment and treatment.